Strategi Modifikasi Perilaku untuk Gaya Hidup Sehat dalam Mengurangi Perilaku Bermain Tiktok - Srirahayu, Cut; Setianingsih, Endang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid growth of TikTok has significantly changed digital behavior, particularly among adolescents and young adults. Although the platform offers entertainment, educational content, and social interaction, excessive use has been associated with unhealthy lifestyles, including poor sleep quality, reduced physical activity, decreased productivity, and psychological problems such as stress and anxiety. This study aims to synthesize recent evidence on behavior modification strategies that can reduce excessive TikTok use and promote a healthier lifestyle. The study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Articles were retrieved from Scopus, ScienceDirect, SpringerLink, PubMed, Google Scholar, and Garuda databases, with publications limited to the period 2020–2026. Thirty-five eligible studies were analyzed using thematic analysis. The findings indicate that integrated behavior modification strategies, including self-monitoring, stimulus control, goal setting, habit substitution, self-regulation, and social support, are more effective than single-component interventions in reducing problematic TikTok use. These strategies not only decrease screen time but also contribute to improved sleep quality, increased physical activity, enhanced productivity, and better psychological well-being. The review concludes that behavior modification provides a comprehensive and sustainable approach to encouraging healthy digital lifestyles and may serve as a conceptual foundation for future intervention programs and digital health promotion.